EFFECT OF FINANCIAL RATIOS ON PROFITABILITY - kannia permatasari gunawan (COMPETITIVE, 2022)
The global economic phenomenon that occurred eventually had an impact on ASEAN countries, especially in Indonesia. Such as the tightening of monetary policy carried out by the United States and also the trade war between the United States and China. This study aims to determine the effect of the Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR) and Operational Cost of Operating Income (BOPO) on Return On Assets (ROA) at BUMN Bank Indonesia 2010-2019. Due to the small and narrow population of 4 banks, the sample is only 4 state-owned banks in Indonesia and the sampling technique used in this study is saturated sampling method. The statistical analysis used is descriptive analysis and verification analysis using multiple linear regression analysis, t test and F test. Based on the results of the analysis, it is found that LDR has no effect on ROA, CAR has no effect on ROA and BOPO has a significant negative effect on ROA. The Adjusted R Square value is 0.816. This shows that the independent variables in this study (LDR, CAR and BOPO) have an effect of 81.6% on the dependent variable (ROA) while 18.4% are influenced by other factors not examined.